2020
DOI: 10.2196/15329
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance of Health Wearables Data: Participatory Workshop on Barriers, Solutions, and Expectations

Abstract: Background The ubiquity of health wearables and the consequent production of patient-generated health data (PGHD) are rapidly escalating. However, the utilization of PGHD in routine clinical practices is still low because of data quality issues. There is no agreed approach to PGHD quality assurance; therefore, realizing the promise of PGHD requires in-depth discussion among diverse stakeholders to identify the data quality assurance challenges they face and understand their needs for PGHD quality a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Currently, there exist many consumer-grade devices that promise to improve health and wellness without scientific evidence substantiating such claims; hence, there is an urgent need for clinically validated devices and wearables [ 9 , 43 ]. The quality assurance (and measurement accuracy) of technologies has been questioned before and several challenges were identified by previous studies [ 39 , 44 ]. The findings of Abdolkhani et al [ 44 ] indicated that technical and policy standards need to be developed to guarantee the quality of data generated from wearables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there exist many consumer-grade devices that promise to improve health and wellness without scientific evidence substantiating such claims; hence, there is an urgent need for clinically validated devices and wearables [ 9 , 43 ]. The quality assurance (and measurement accuracy) of technologies has been questioned before and several challenges were identified by previous studies [ 39 , 44 ]. The findings of Abdolkhani et al [ 44 ] indicated that technical and policy standards need to be developed to guarantee the quality of data generated from wearables.…”
Section: Discussionmentioning
confidence: 99%
“…The quality assurance (and measurement accuracy) of technologies has been questioned before and several challenges were identified by previous studies [ 39 , 44 ]. The findings of Abdolkhani et al [ 44 ] indicated that technical and policy standards need to be developed to guarantee the quality of data generated from wearables. Besides the need for such standards, it is important to validate the wearables by “fit-for-purpose validation” [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, for some MTurk experiments, disparities have been evidenced between laboratory and online data collection (Crump et al, 2013 ). Further clarifications about quality, such as consistency or interpretability (Abdolkhani et al, 2020 ), are also needed for data collected using wearables.…”
mentioning
confidence: 99%
“…The main limitation of this framework is that it does not include quality control measures for SDV. Abdolkhani et al [ 46 ] discussed wearable health data solutions for RWD quality control in a workshop format. However, this study only proposed 5 general solutions for the attributes of health data and has not yet formed a complete theoretical framework.…”
Section: Discussionmentioning
confidence: 99%